Given that x and y satisfy a proportional relationship, then the next equation relates the variables:
y = kx
where k (a constant) can be obtained with a pair of values (x,y). In this case:
![k=(y)/(x)=(2)/(-1)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/54f5gqkkwej6qyjmj1dv1iljz6cm2mspuh.png)
Now, we need to select two values from the list that satisfy this value of k.
![k=(-6)/(3)=-2](https://img.qammunity.org/2023/formulas/mathematics/college/x3txxm2ydy6qimyyqisqxsu786gj4wb11a.png)
that is, y = -6 and x = 3
x | y
-1 | 2
3 | -6